Pengaruh Faktor Risiko Terhadap Keputusan Petani dalam Memilih Saluran Pemasaran Kubis - Amri, Azrarul; Maskar, Rismaladewi; Rahman, Anita (Universitas Batangahari Jambi, 2025)
Cabbage is one of the widely cultivated crops in Indonesia. However, there are certainly risks that will reduce production or even result in losses. This study aims to analyze farmers' decisions in choosing cabbage farm marketing channels, and analyze the effect of production risk, marketing risk, and cost risk on farmers' decisions in choosing cabbage marketing channels. The research was conducted in Erelembang Village, Tombolopao District, Gowa Regency by taking 98 respondents of cabbage farmers. The data that has been obtained then analyzed using descriptive analysis and binary logistic linear regression analysis. The results showed that farmers were more likely to choose intermediary traders (82.7%) than selling cabbage to the local market (17.3%). In addition, production risk affects the decision of farmers in choosing marketing channels, where the higher the risk of production, farmers are more likely to sell cabbage to intermediary traders.